2011
DOI: 10.1097/jto.0b013e31822e7256
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trials of Imatinib Mesylate and Docetaxel in Patients with Metastatic Non-small Cell Lung Cancer and Head and Neck Squamous Cell Carcinoma

Abstract: We do not recommend further investigation of this regimen in the aerodigestive tumors. Future investigations in PDGFR tyrosine kinase inhibitors should be used with caution in combination with taxanes and validation of the potential predictive or prognostic biomarkers stromal PDGFRα/β, and tumor cell PDGFRβ are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…In concequence, we set up the above study to analyze its potency in HNSCC cell lines to confirm these effects. The concentrations of imatinib used in our experiments were within the range that is achieved in a clinical trial (37). Similarly, the concentrations of carboplatin used in this study are clinically relevant.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In concequence, we set up the above study to analyze its potency in HNSCC cell lines to confirm these effects. The concentrations of imatinib used in our experiments were within the range that is achieved in a clinical trial (37). Similarly, the concentrations of carboplatin used in this study are clinically relevant.…”
Section: Discussionmentioning
confidence: 59%
“…In former studies imatinib also showed inhibitory impact on the PTK receptor c-kit and on its PTK activity (33,35). Thus, imatinib has antitumor activities towards adenocarcinoma, e.g., colon cancer, and its antitumoral effects have also been shown in non-small cell lung cancer and HNSCC (36,37). In concequence, we set up the above study to analyze its potency in HNSCC cell lines to confirm these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imatinib also showed an inhibitory effect on the catalytic activity of PDGFR and c-kit tyrosine kinases. It is used for the treatment of several malignancies, such as colon adenocarcinoma and non-small cell lung cancer (37)(38)(39). The aim of the present study was to investigate the effects of imatinib and 5-FU on HPV16-associated HNSCC compared to non-HPVinduced HNSCC and their impact on the expression of MMP-2 and MMP-14 in order to examine the potency of chemotherapeutic agents in HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated that PDGF overexpression is associated with increase of melanoma cells proliferation and increased pericyte abundance (Furuhashi et al, 2004). Unfortunately, treatment with imatinib (TKR inhibitor specific to PDGFRβ) has not produced encouraging results in patients with metastatic non-small cell lung cancer (Tsao et al, 2011). Conversely, dual PDGFRβ/VEGFR inhibition is effective for treating multiple stages in tumorigenesis, particularly in solid tumors with high pericyte coverage (Bergers and Hanahan, 2008).…”
Section: Need For Pro-angiogenic Therapy?mentioning
confidence: 99%